Antioxidant capacity and total phenols richness of Cistanche violacea hosting Zygophyllum album - Mohamed Debouba; Rafik Balti; Sami Hwiwi; Sami Zouari (International Journal of Phytomedicine, 2012)
Cistanche violacea is an Orobanchaceae holoparsite hosting chenopodiaceous, including Zygophyllum album. While Cistanche violacea, is known to have edible uses in the folk medicine, no data have been reported before. In the present study, chemical assays were undertaken in order to emphasize the Cistanche violacea antioxidant capacity and total phenols richness. Our data showed higher phenolic contents were measured in Cistanche flowers and Zygophyllum leaves, however Cistanche bulb was the most enriched in flavonoïds. Antioxidant activities were evaluated in methanolic extract of Cistanche violacea flowers and bulb among the host Zygophyllum album leaves. Cistanche flowers and Zygophyllum leaves exhibited the strongest scavenging 2,2-diphenyl-2-picrylhydrazyl radical (DPPH) activity. The metal chelating activity was the highest in Cistanche bulb and Zygophyllum leaves compared to Cistanche flowers. Conversely, the ferric reducing power was significantly higher in Cistanche flowers relative to its bulb and Zygophyllum leaves